Diversity and spatial distribution of Order Diptera from Kuala Keniam National Park, Pahang, Malaysia - IBRAHIM NUR AMIN; KHAIRUDIN NURUL FATHIAH; NIZAM NUR ‘ALIYAA; MOHAMMAD NASER NUR BADRINA; MD YUSOF NUR NADIAH; KAMARUDIN SITI HASNAH; MOHD ZAZI NORHAFIZAH; MOHD HATTA SITI KHAIRIYAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Amin IN, Fathiah KN, ‘Aliyaa NN, Badrina MNN, Nadiah MYN, Hasnah KS, Norhafizah MZ, Khairiyah MHS. 2023. Diversity and spatial distribution of Order Diptera from Kuala Keniam National Park, Pahang, Malaysia. Biodiversitas 24: 4668-4674. A study on the diversity and distribution of order Diptera was conducted in different Kuala Keniam National Park, Malaysia landscapes. Three malaise traps were placed in three landscapes: the forest fringe, middle forest, and inner forest. A total of 1920 Diptera were recorded from 19 families and 109 morphospecies of order Diptera. Anthomyiidae, Calliphoridae, Pipunculidae, Scenopinidae, Ulidiidae, Tephritidae, Ceratopogonidae, Stratiomyidae, Asilidae, Syrphidae, Tipulidae, Ephydridae, Cecidomyiidae, Dolichopodidae, Phoridae, Culicidae, Muscidae, Sciaridae, and Drosophilidae were the identified families. The family with the highest number of individuals collected was Phoridae, with 89 individuals (5 morphospecies) collected from the forest fringe, followed by 271 individuals (6 morphospecies) from the middle forest and 697 individuals from the inner forest (7 morphospecies). Pipunculidae had the least collected individuals, with only one in the inner forest. The forest fringe recorded the highest Shannon-Wiener Diversity Index (2.13), followed by the middle forest (1.68) and the inner forest (1.04). The forest fringe also recorded the highest Evenness Index and Margalef Richness Index with 0.44 and 3.16, respectively. The distribution of Diptera differed significantly along the environment gradients from the forest fringe to the inner forest (p<0.05), and the pairwise comparison showed that the difference comes from Trap 2 and Trap 3 (p<0.001). The forest fringe was more diversified than the middle and the inner forest, even though the number of individuals was low. Vegetation types and sunlight might be the reasons behind this discovery. The results from this study can be used as baseline data for future reference on the diversity of Diptera from the forest reserve.